2002
DOI: 10.1002/clc.4960251106
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of C‐Reactive Protein, Fibrinogen, Interleukin‐6, and Macrophage Colony Stimulating Factor in Severe Unstable Angina

Abstract: SummaryBackground: Inflammatory process plays an important role in the pathogenesis of acute coronary syndromes.Hypothesis: The study was undertaken to evaluate whether admission levels of C-reactive protein (CRP), fibrinogen, interleukin-6 (IL-6), and macrophage colony stimulating factor (MCSF) can predict short-term prognosis in patients with unstable angina.Methods: C-reactive protein, fibrinogen, IL-6, and MCSF were measured on admission in 141 consecutive patients, aged 59 ± 10 years, with unstable angina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…(16,17) Moreover, some authors observed how increased MCSF levels in patients with unstable angina may predict a worse prognosis during in hospital stay and in a mid to long term period. (16,(18)(19)(20)(21) This study confirmed the importance of MCSF as a prognostic marker in acute coronary syndrome with its levels higher in patients with worse in hospital stay and more diseased coronary vessel. Moreover, for the first time the authors have observed the abserved the absence of significant statistical differences of its concentrations between STEMI and NSTEMI patients.…”
Section: Discussionsupporting
confidence: 73%
“…(16,17) Moreover, some authors observed how increased MCSF levels in patients with unstable angina may predict a worse prognosis during in hospital stay and in a mid to long term period. (16,(18)(19)(20)(21) This study confirmed the importance of MCSF as a prognostic marker in acute coronary syndrome with its levels higher in patients with worse in hospital stay and more diseased coronary vessel. Moreover, for the first time the authors have observed the abserved the absence of significant statistical differences of its concentrations between STEMI and NSTEMI patients.…”
Section: Discussionsupporting
confidence: 73%
“…Lp(a) may act as an acute-phase reactant (24 ) and thus possibly contribute to acute cardiac events. Moreover, many studies have demonstrated a significant relationship between Lp(a) and CRP (13,14 ) and other inflammatory factors, such as fibrinogen, interleukin-6 (7 ), complement 3 and 4 (8 ), and soluble cellular adhesion molecules (9 ), which suggests that Lp(a) may be involved in atherogenesis through an inflammatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Extensive data have shown that CRP levels provide independent prediction of adverse cardiovascular events such as myocardial infarction and stroke. (11)(12)(13)(14)(15) The role of CRP concentrations in identifying risk for complications after cardiac surgery is increasingly under investigation. (16,17) A link between CRP levels and atrial fibrillation supports the notion that inflammation enhances susceptibility to the arrhythmias regardless of whether the surgery is performed with our without cardiopulmonary bypass.…”
Section: Introductionmentioning
confidence: 99%